2022
DOI: 10.1055/s-0041-1741545
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Electrical Bicycle Road Accidents

Abstract: Introduction The use of electric bicycles (EBs) among children younger than 18 years of age is rapidly increasing worldwide and becoming a substantial contributor to road accidents. We analyzed patterns and severity of pediatric bicycle-related injuries, comparing children riding EBs and classic bicycles (CBs). Materials and Methods This was a retrospective study (January 2016–December 2018) of patients arriving at our medical center due to a bicycle accident. Data were collected from medical records… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…Concussions and internal injuries were also more common for e-bike injuries compared to bicycle injuries. These findings are concordant with the findings of a single-institution pediatric study conducted in Israel, which demonstrated higher ISS and more frequent loss of consciousness among injured e-bike riders compared to pedal bike riders [ 16 ]. However, a single-center study conducted in Switzerland reported that e-bike injury patterns were similar to those observed for pedal bicycles but not motorcycles [ 17 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Concussions and internal injuries were also more common for e-bike injuries compared to bicycle injuries. These findings are concordant with the findings of a single-institution pediatric study conducted in Israel, which demonstrated higher ISS and more frequent loss of consciousness among injured e-bike riders compared to pedal bike riders [ 16 ]. However, a single-center study conducted in Switzerland reported that e-bike injury patterns were similar to those observed for pedal bicycles but not motorcycles [ 17 ].…”
Section: Discussionsupporting
confidence: 89%
“…Hypotheses to explain our finding of more severe injuries with e-bikes specific to children include issues related to speed as well as behavior. E-bikes achieve higher average speeds than pedal bicycles [ 16 ]. Although e-bikes are legally speed limited in many states, assisted speed can reach 28 mph, and consumer modifications may lead to even higher speeds [ 14 ].…”
Section: Discussionmentioning
confidence: 99%